2020
DOI: 10.3389/fendo.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Driven Changes in Adipogenesis in Different Fat Depots Are Related to Obesity

Abstract: Subcutaneous (sc) and visceral (vis) adipose tissue (AT) contribute to the variability in pathophysiological consequences of obesity and adverse fat distribution. To gain insights into the molecular mechanisms distinguishing vis and sc fat, we compared the transcriptome during differentiation of immortalized adipocytes from murine epididymal (epi) and inguinal (ing) AT. RNA was extracted on different days of adipogenesis (−2, 0, 2, 4, 6, 8) and analyzed using Clariom TM D mouse assays (Affymetrix) covering >21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Our methylation analysis results confirm findings previously published on homeobox and other genes involved in adipogenesis and browning of white AT. 36 37 Also, when comparing epiAT in the IR versus the IS state, we found a hypermethylated DMR close to CYP2E1 , the gene product of which is associated with oxidative stress and cellular damage in non-alcoholic fatty liver disease (NAFLD), obesity and T2D. 38 However, it should be noted that most of these previous findings are either from studies in mice, human peripheral blood leucocytes or other AT biopsies and not from epiAT, where data until now remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Our methylation analysis results confirm findings previously published on homeobox and other genes involved in adipogenesis and browning of white AT. 36 37 Also, when comparing epiAT in the IR versus the IS state, we found a hypermethylated DMR close to CYP2E1 , the gene product of which is associated with oxidative stress and cellular damage in non-alcoholic fatty liver disease (NAFLD), obesity and T2D. 38 However, it should be noted that most of these previous findings are either from studies in mice, human peripheral blood leucocytes or other AT biopsies and not from epiAT, where data until now remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported that HOXC10 was involved in regulating anterior/posterior pattern specification ( 22 – 24 ), limb regeneration ( 25 27 ), and lumbar motor neuron differentiation ( 28 31 ). HOXC10 is also associated with angiogenesis ( 32 ), fat metabolism ( 33 38 ), and sex regulation ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 26 ) comparing lipomas and subcutaneous adipose tissue of the same patient, and second, a study by Breitfeld et al. ( 27 ) comparing adipogenesis in murine inguinal and epididymal fat depots. We found an overlap of 36 genes ( Table S3 ), including some known regulators of adipogenesis such as FOXO1 ( 28 ) and genes such as RNF144B , which has no known function in adipose tissue yet.…”
Section: Resultsmentioning
confidence: 99%